Penerapan Kurikulum Cinta untuk Mencegah Perundungan (Bullying) di Sekolah Menengah Atas (SMA) (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This study aims to explore and evaluate the implementation of the Curriculum of Love as a comprehensive preventive approach to addressing bullying in Senior High Schools. Bullying, defined as repeated negative behaviors intended to harm others through verbal, physical, or social actions, has become a serious problem in schools across Indonesia. Its effects on victims include physical and psychological health issues, reduced self-confidence, and in severe cases, suicidal thoughts. The research uses a literature review method, analyzing various academic sources such as journals and scholarly reports because the topic is closely related to theoretical concepts and theological values. The Curriculum of Love is a humanistic, holistic, and transformative educational model that emphasizes love, empathy, care, and compassion as central to all learning activities. Its core values of love, tolerance, and harmony form the foundation for promoting positive behavior. Findings indicate that this curriculum effectively addresses the complex causes of bullying, including individual, family, and social factors, by systematically instilling these core values. Implementation involves cultivating love for God to strengthen moral responsibility, love for fellow humans to foster respect and empathy, and practical activities such as role play, classroom companion programs, peaceful conflict resolution training, and teacher modeling. The Curriculum of Love creates a safe and supportive school environment and serves as an essential preventive and transformative educational strategy.